Article Commentary: Rural Pediatric Surgery. Issue 3 (March 2015) - Nakayama, Don K.
Published outcome studies support regionalization of pediatric surgery, in which all children suspected of having surgical disease are transferred to a specialty center. Transfer to specialty centers, however, is an expensive approach to quality, both in direct costs of hospitalization and the expense incurred by families. A related question is the role of well-trained rural surgeons in an adequately resourced facility in the surgical care of infants and children. Local community facilities provide measurably equivalent results for straightforward emergencies in older children such as appendicitis. With education, training, and support such as telemedicine consultation, rural surgeons and hospitals may be able to care for many more children such as single-system trauma and other cases for which they have training such as pyloric stenosis. They can recognize surgical disease at earlier stages and initiate appropriate treatment before transfer so that patients are in better shape for surgery when they arrive for definitive care. Rural and community facilities would be linked in a pediatric surgery system that covers the spectrum of pediatric surgical conditions for a geographical region.